Q: What is 18 plus -3 minus -6?

Write your answer...

Submit

Related questions

18

15 + 3 - 6 / 2 * 6 = 15 + 3 - 3 * 6 = 15 + 3 - 18 = 18 - 18 = 0

3 + 3 = 6 6 x 3 = 18 18 - 3 = 15 15 + 3 = 18

(18/3) + 6 -(2 x 4) = 4

-6 x -3 = 18 + (-6) = 12

Zero

3 + 6 - 2 + 14 - 3 + 2 = 20

3 minus 3/18 is 2 5/6

-9

(x - 3)(x^2 + 6)

That factors to (x - 3)(x + 6)

1 + 6 + 9 - 8 + 4 - 5 + 2 + 3 = -6

minus 6, plus 3, minus 6, plus 3...

x2 - 9x + 18 = (x - 3)(x - 6)

(-6) x (-3) = 18 (-10) x (-9) = 90 18 - 90 = -72

X2 + 3X - 18 Ask yourself, what two factors of - 18 add to 3? (X + 6)(X - 3) -----------------

6 plus 6 plus 6 is 18. It is the same as 6 x 3 = 18

29 + - 3 + 6 + - 41 + 18 = 29 - 3 + 6 + 41+ 18 =93

-3

6 plus 4 minus 2 plus 2 minus 3= 7 :)

34 minus 6

24 ; 72; 18; 23; 17.

cheater == 2[x-3]+3[x-2]=18 2x-6+3x-6=18 5x-12=18 5x=30 x=30/5=6

9.

-6 times 12 plus 14 minus 3 is equal to -61.